Fatores associados à esperança de idosos cuidadores de idosos - Souza, Érica Nestor (Universidade Federal de São Carlos, 2016)
The longevity associated with chronic degenerative health problems, contributes to the increase of older people with functional limitations, disabilities and the need for care. The role of caregiver can trigger a series of impacts on the physical and mental health. However, hope can be psychosocial feature of these caregivers to deal with the difficulties on the experience of care. The objective this study is identify factors associated with the hope of elderly caregivers of elderly. This is a quantitative study, descriptive and crosssectional. The sample consisted of 301 subjects who played role of caregivers registered in the Family Health Units in a city in São Paulo state. Data were collected through individual interviews, using the following instruments: Characterization of the Subjects; Herth Hope Index (HHI); Pinto Pais - Ribeiro Spirituality Scale (PP-RSS); Geriatric Depression Scale (GDS); Evaluation of Fragility; Perceived Stress Scale; Mini-Mental State Examination (MMSE); Inventory of Coping Strategies; Zarit Caregiver Burden Interview (ZBI). Analyses were performed using multivariate statistics (multinomial logistic regression). The results showed that the mean score of EEH was 40.9 (± 5.4). As for PP-RSS, mean the belief domains and hope / optimism were 3.85 and 3.39, respectively. The most widely used coping strategy was "the expression of negative emotions", averaging 19.8 points. In GDS, the majority (77.8%) had no depressive symptoms. As for the perceived stress, the average score was 19.0 points. In the MMSE, the majority (61%) showed evidence of cognitive impairment. The average obtained in the ZBI was 17.9 and in the evaluation of fragility, the majority (56.8%) was pre-fragile. With regard to factors associated with hope, according to the regression model were: spirituality, stress, old age, caregiver without income, not receive help affective / emotional and care for 6- 10 hours a day. Therefore highlights the need for public policies and care actions to these elderly caregivers elderly, as well as interventions aimed at stimulating hope with emphasis in the associated factors identified.
Factors associated with the hope of elderly caregivers of elderly
Keywords: Idosos; Cuidadores; Esperança; Gerontologia; Elderly; Caregivers; Hope; Gerontology; CIENCIAS BIOLOGICAS